2005
DOI: 10.2514/1.3543
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Loading of a Tension Kite

Abstract: A theory is presented for the optimum shape of tension kites based on lifting-line theory combined with the requirement that the kite shape and tension be in equilibrium everywhere with the forces normal to it. The flying shape of the kite then emerges as part of the solution, along with the distribution of twist, which must be built into any particular kite to achieve the required loading. Results are presented first for a kite in ideal flow, when all the important parameters scale with the lift coefficient, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Sanchez [22] has started from Lagrangian equations of motion to formulate a model for longitudinal dynamics of a kite and uses this to develop a controller for this symmetric flight mode. Stevenson [23] deals with the existence of possible static equilibrium points and Jackson [24] investigates the shape of the kite in relation to its optimal loading using a static analysis based on Prandtl's lifting line theory.…”
Section: Introductionmentioning
confidence: 99%
“…Sanchez [22] has started from Lagrangian equations of motion to formulate a model for longitudinal dynamics of a kite and uses this to develop a controller for this symmetric flight mode. Stevenson [23] deals with the existence of possible static equilibrium points and Jackson [24] investigates the shape of the kite in relation to its optimal loading using a static analysis based on Prandtl's lifting line theory.…”
Section: Introductionmentioning
confidence: 99%
“…Diameter of the rope kite trace can be simply estimated as a two-dimensional equilibrium of the force acting on the rigid kite system at a given moment using a circular cylinder (Jackson, 2005;Williams et al, 2007;Vaikil and Green, 2009), as shown in Fig. 6.…”
Section: Resultsmentioning
confidence: 99%
“…These data can be evaluated experimentally (De Wachter 2008;Dadd et al2010;Behrel et al 2018ab;Roncin et al 2020) or numerically by means of methods like lifting line (Leloup et al 2012;Duport et al 2015;Jackson et al 2005), VLM (Gohl et al 2005), panel methods or RANSE (Reynolds-Average Navier-Stokes Equations) simulation (de Wachter 2008;Duport et al 2015;Maneia et al 2013).…”
Section: State Of the Artmentioning
confidence: 99%